StoryBranding : creating standout brands through the power of story - Signorelli, Jim (Greenleaf Book Group Press, 2012)
"To help brands resonate with their audiences, the author takes you step by step through StoryBranding's six Cs--a process that shows how to approach the development of all brand communications the way story writers approach their characters, plots, and themes."--Jacket.